FUNGSI PEMERIKSAAN DISMISSAL DALAM PERADILAN TATA USAHA NEGARA - Dezonda R. Pattipawae (SASI, 2014)
Law No. 5 of 1986, as amended and supplemented by Law No. 9 of 2004 concerning the State Administrative Court, and also in the explanation, the term process of dismissal is not known, but the substance of meanings provided for in Article 62 Court Law. The process of dismissal or a consultative meeting of the screening process to suit the incoming State Administrative Court. Events in the consultative meeting or dismissal examinations conducted by deliberation whether the case is accepted or not. The existence of the background of this dismissal is based on a claim that not all can be received at the Administrative Court so that the process is solid filtered dismissal cases that entered in the Administrative Court. The dismissal process must be passed every lawsuit that goes to the administrative court. It was to assess the feasibility of a lawsuit proceed to the next stage of the trial. In the process of dismissal, accompanied by the Chairman of the Administrative Court clerks who recorded the course of the examination file. "If adopted, the chairman of the administrative court will appoint a panel of judges, but if not accepted, will be issued the determination of dismissal, thepartiesobjected to the determination of dismissal can take the fight, and the chairman of the State Administrative Court would reassess. Assessment isa lawsuit under the authority Administrative Courtor not to prosecute. It could have entered his complaint to the administrative court but after examination, the general judicial authority,not the administrative court.